Nicho temporal de aves e mamíferos de médio e grande porte em áreas do ecótono Amazônia-Cerrado - Fauth, Scarlet Alice Carvalho (2023)
The temporal niche of a fauna species concerns the distribution of locomotion activities over a 24-hour daily cycle. There are a variety of daily patterns of animal activity that can be classified as nocturnal, diurnal, twilight or even without well-defined activity peaks, called cathemerals. Interspecific interactions within a biological community can result in sharing (temporal niche overlap between predator and prey) or temporal niche differentiation (niche separation between competitors), depending on the species composition in the community. Few studies on the temporal niche of species in biological communities provide evidence of behavioral processes of population regulation, which occur both top-down and bottom-up. This is an analogy to the processes of the same name that regulate food webs. Thus, the top-down behavioral process is evidenced when a species adjusts its activity schedule to avoid predators and competitors. In this case, low temporal niche overlap between predator and prey and between competitors is expected. Likewise, the bottom-up behavioral process is evidenced when predators adjust their activity schedules to facilitate encounters with potential prey species. In this case, high temporal niche overlap between prey and predators is expected. One way to investigate these activity patterns is to use camera traps. Based on camera trap footage, we analyzed the activity times of birds and medium and large mammals in 30 forest remnants in an Amazon-Cerrado ecotone region, located in Arco do Desmatamento, in northern MT, Brazil. Between November 2021 and January 2023, we sampled narrow riparian forests that function as ecological corridors to the riparian forest of the Teles Pires River. We created rosette diagrams to represent the activity times of each species of interest and used Rayleigh analysis to investigate whether recorded species exhibit activity peaks throughout the circadian cycle. Furthermore, temporal niche overlap between species pairs was examined, encompassing potential predation and competition relationships, based on trophic niche similarity and close phylogenetic relationship. We obtained a total of 1,800 camera trap exposure days, which is equivalent to 43,200 hours of sampling. During this period, we obtained 1,103 records of birds and medium and large mammals, 113 records of birds and 990 records of mammals. The records of five species of medium and large birds and 17 species of mammals reflect a low species richness in the Amazon- Cerrado ecotone region compared to other surveys carried out in different regions of the Amazon. Our data highlight the greater potential for encounter between species with high temporal niche overlap in a region with reduced availability of spatial niches, due to the accentuated loss of habitat in the study region. Our research contributes with information on the temporal niche of species with the application of sampling with camera traps, being useful for future population monitoring to consider the activity times of these species in the region, increasing the efficiency of species sampling, which allows the understanding of how different species interact over time, in addition to allowing more effective management of these ecosystems.